Pregnancy outcomes of women with Eisenmenger syndrome: A single-center study. (1st March 2023) - Liu, Yang; Li, Yanna; Zhang, Jun; Zhao, Yichen; Liu, Kemin; Li, Jiachen; Zhao, Mingming; Gu, Hong; Fan, Xiangming; Wang, Jiangang
Abstract: Background: To explore the outcomes of mothers with Eisenmenger syndrome (ES) and their offspring. Methods: Pregnant women with ES admitted to the Beijing Anzhen Hospital between 2010 and 2019 were retrospectively analyzed and followed up. Results: Forty-two parturient women with ES were recruited, with an average age of 26.7 years (standard deviation [SD], ±4.0 years). The average gestational age was 33.7 weeks (SD, ±2.5 weeks). The average percutaneous oxygen saturation was 84.1 (±9.2), and 40 (95.2%) had caesarean delivery. The average pulmonary artery systolic pressure was 107.5 mmHg (SD, ±20.3 mmHg). Twelve (28.6%) women experienced pulmonary hypertensive crisis; 11 (26.2%) of these women died. Regarding the offspring, the average fetal weight was 1778.1 g (SD, ±555.3 g), six (14.3%) died, and congenital heart disease was diagnosed in three (7.1%). There were significant differences in age, gestational age, percutaneous oxygen saturation, Apgar score, and heart failure between the maternal death and non-death groups ( P  < 0.05). Death was mainly related to pulmonary hypertensive crisis and heart failure. Conclusions: We recommend pregnancy termination if ES occurs during early pregnancy; however, patients should be informed of the risks if it occurs during late pregnancy. Multidisciplinary cooperation should be strengthened to improve the prognosis of the mothers and their offspring. Graphical abstract: Although pregnancy should be discouraged in women with Eisenmenger Syndrome (ES), this case series demonstrates that ES pregnancies can be successfully managed with coordinated multi-specialist input care and proper monitoring for preventing adverse maternal and fetal outcomes. These findings give a little hope to advanced gestational age pregnancies complicated with ES. MDT: Multi disciplinary team. Unlabelled Image